Impact of the Experimental Method on Problem-Solving Skills in Early Childhood - Hajar Yaumil Faizah; Ika Budi Maryatun (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Ilmu Pendidikan, Universitas Negeri Makassar, 2025)
This study aims to determine and analyse the impact of experimental methods on the problem-solving skills of early childhood students in Kertosono District. This study uses a quantitative approach with an ex post facto type. The population in this study consists of early childhood education teachers in the Kertosono District. The sampling technique employed is purposive sampling, involving a total of 31 teachers. The instruments used were a questionnaire and an interview. The data analysis technique used the ANOVA test. The results of the study indicate that there is a significant influence between the experimental method and the problem-solving abilities of young children in Kertosono District, with a significance value of 0.000 < 0.05. Based on the coefficient of determination, problem-solving skills are influenced by the experimental method by 85%. From these results, it can be concluded that the more intensive the application of the experimental method in the learning process of young children, the greater their problem-solving ability will be.